A qualitative exploration of the barriers and facilitators to the implementation of the alcohol assertive outreach model. - Scoles, Laura H; Mylonas, Nikolaos; Priyam, Aansha; Blood, Stephen; O'Donnell, Amy; Drummond, Colin; Lovell, Karina; Kaar, Stephen J (Alcohol & Alcoholism, 2025)
Alcohol use disorder has adverse implications for individuals' health, utilisation of healthcare services, and societal costs. There are a group of individuals who frequently attend hospital for alcohol-related issues, have complex co-morbid needs, and experience barriers to engaging with specialised alcohol treatment services. To support these individuals and reduce healthcare system costs, Alcohol Assertive Outreach Treatment (AAOT) has been recommended. However, AAOT is not routinely used in the UK. Understanding the determinants of the implementation of AAOT can increase its utilisation and effectiveness. This study therefore employed the Consolidated Framework for Implementation Research (CFIR) framework to highlight barriers and facilitators to the successful and sustainable implementation of AAOT. Semi-structured interviews were conducted with twenty AAOT team staff members (team managers and outreach workers) from two North West England AAOT teams. Twenty-eight stakeholders (clinicians, commissioners, policy makers and academics across England) were also interviewed, who were considered to be key contributors to AAOT implementation, both within and external to North West England. Framework analysis based on the CFIR was conducted, whilst allowing for inductive coding where appropriate. Overall, participants recognised AAOT as acceptable and beneficial. Three main themes were identified: organisational and individual level factors, including team culture and staff characteristics; systemic partnerships and interagency communication; and an adaptable model driven by research and evaluation. Each theme relates to various CFIR domains and constructs which were perceived to influence the implementation of AAOT. Readers are encouraged to consider the findings in the development and implementation of AAOT teams, new or existing.